Panduan toleransi agama dalam hubungan Muslim-Kristian Malaysia melalui pendekatan Ismail al-Faruqi / Nur Farhana Abdul Rahman - Nur Farhana , Abdul Rahman (2016)
Religious tolerance has been widely discussed and instigated in either direct or indirect manner. However, there are many unresolved issues in instigating Muslim-Christian relation in Malaysia due to lacking of proper references and guidance. Thus, the purpose of this research is to analyze the religious tolerance phenomenon in Malaysia, based on the al-Fārūqī approach of religious tolerance from the perspective of Muslim and Christian religious leaders. Al-Fārūqī argued that religious tolerance is best to be approached by phenomenology and meta-religion methodology. Grounding on this platform, this qualitative research uses al-al-Fārūqī’s approach of phenomenology in understanding the issue. This research employs in-depth interview session with six Muslim representative religious leaders and five Christian representative religious leaders. Data from the interviews were analyzed thematically using Atlas Ti software. The findings show that the most important component of religious tolerance phenomenon in Muslim-Christian relation are; (i) recognition of religious diversity, and (ii) willingness to live in harmony. This study recommends three imperative approaches in developing the religious tolerance which are understanding of religion, interfaith dialogue and guided comparative religion approach. However, there are some relevant limitations that must be acknowledged in establishing a religious tolerance in a society. Hence, grounded on the religious leaders’ views, the al-Fārūqī approach with some modifications is still pertinent and feasible to be implemented in Malaysia.